2013
DOI: 10.1021/ma401313e
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of the Chain End and Branching Units in Poly(vinylidene fluoride-co-tetrafluoroethylene)

Abstract: 2D-NMR techniques were used to identify the detailed structures of chain end and branching units in poly(vinylidene fluoride-co-tetrafluoroethylene), poly(VDF-co-TFE). Atomic connectivity information was provided by selective 19 F− 19 F COSY (correlation spectroscopy), 19 F{ 1 H} gHETCOR (gradient heteronuclear correlated), and 1 H{ 13 C} HSQC (heteronuclear single quantum correlation) experiments. Diffusion ordered spectroscopy (DOSY) and spin− lattice relaxation (T 1 ) data permitted distinction of backbone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…On the other hand, selective COSY experiments provide better digital resolution and sensitivity. This results in less time and stronger cross‐peaks because anti‐phase cross‐peak components are well resolved . It has been already shown that 19 F– 19 F gCOSY can provide valuable information about microstructural assignments in the polymer main chains .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, selective COSY experiments provide better digital resolution and sensitivity. This results in less time and stronger cross‐peaks because anti‐phase cross‐peak components are well resolved . It has been already shown that 19 F– 19 F gCOSY can provide valuable information about microstructural assignments in the polymer main chains .…”
Section: Resultsmentioning
confidence: 99%
“…It has been already shown that 19 F– 19 F gCOSY can provide valuable information about microstructural assignments in the polymer main chains . The experiment gCOSY was also employed for chain end analysis of a fluorinated polymer . For example, the cross‐peak between CF 2 of HFP at −103.98 ppm and CF 3 of HFP at −71.35 ppm are important examples of the weakest through‐bond correlations by gCOSY.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that 19 F detected DOSY experiments could be used to distinguish between the resonances of polymer chain-ends and other branching structures in a series of fluoropolymers. [40][41][42] Generally, the performance of 19 F NMR experiments on fluoropolymers creates some unique complications that often interfere with detection of important signals. [39] These factors include: (1) the presence of many scalar couplings among 1 H, 19 F and 13 C; (2) the large magnitudes of many 19 F homonuclear couplings (especially 2 J FF ); (3) the large 19 F chemical shift range; and (4) the low solubility of these materials (which requires that experiments be performed at high temperatures).…”
Section: Introductionmentioning
confidence: 99%
“…[41] These spectra were devoid of the aforementioned problems because the resonances were dispersed over the relatively narrow (50 ppm) CF 2 region of the 19 F chemical shift range, and almost all of the CF 2 fluorines were chemically equivalent. However, problems were encountered in later attempts to study copolymers and terpolymers of VDF containing hexafluoropropylene (HFP).…”
Section: Introductionmentioning
confidence: 99%